Efficacy of an Anatomical Approach in Radiofrequency Catheter Ablation of Idiopathic Ventricular Arrhythmias Originating From the Left Ventricular Outflow Tract. (May 2017) - Yamada, Takumi; Yoshida, Naoki; Doppalapudi, Harish; Litovsky, Silvio H.; McElderry, H. Thomas; Kay, G. Neal
Abstract : Background—: When anatomic obstacles preclude radiofrequency catheter ablation of idiopathic ventricular arrhythmias (VAs) originating from the left ventricular outflow tract (LVOT), an alternative approach from the anatomically opposite side (endocardial versus epicardial or above versus below the aortic valve) may be considered (anatomic ablation). The purpose of this study was to investigate the efficacy of an anatomic ablation in idiopathic LVOT VAs. Methods and Results—: We studied 229 consecutive patients with idiopathic LVOT VAs. Radiofrequency ablation from the first suitable site was successful in 190 patients, and in the remaining 39 patients, it was unsuccessful or had to be abandoned because of anatomic obstacles. In 22 of these 39 patients, an anatomic ablation was successful, and the VA origins were located in the intramural LVOT in 17 patients, basal left ventricular summit in 4, and LVOT septum near the His bundle in 1. The anatomic ablation was highly successful for idiopathic VAs originating from the intramural LVOT (>75%) and lateral LVOT, whereas it was unlikely to be successful for idiopathic VAs originating from the basal left ventricular summit (25%) and sepal LVOT. Conclusions—: When a standard catheter ablation targeting the best electrophysiological measure of idiopathic LVOT VAs was unsuccessful or had to be abandoned because of anatomic obstacles, an anatomic ablation was moderately successful. These idiopathic LVOT VAs with a successful anatomic ablation commonly arose from the intramural LVOT among the left coronary cusp, aortomitral continuity, and epicardium, occasionally the basal left ventricular summit, and rarely the LVOT septum near the His bundle.